STIX padded arnis sticks production and inventory analysis - Tantuco, Johntee T.; King, Patrick Jason L.; Quijano, Christia M.; Oleta, Trisha Anne C.
The study develops the best production plan for STIC, a manufacturer of high quality Arnis equipment and uniforms, specifically for their padded Arnis sticks product, as this has the highest annual use value. April to June 2015 data show that the company had an average inventory level that exceeded the desired buffet stock level of 3,000 padded Arnis sticks. Product aggregation was utilized to minimize random variation effects. The forecasting technique with the least error was determined using the Mean Absolute Deviation and Mean Absolute Percentage Error as measures. From this, the simple average method was used to forecast sales from June 2016 to May 2017. An integer linear programming model was constructed to determine an optimal production plan that minimizes the total cost of production. The results show that optimal production plan exhibits a chase demand strategy in aggregate planning.